Apropriasi Perguruan Tinggi Nahdlatul Ulama pada Era Reformasi - Ruswan Ruswan (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2023)
The Reformation era in Indonesia presents a political ecosystem that has an impact on the development of Nahdlatul Ulama Universities (PTNU). The development of PTNU is important to study so that there is a better understanding of the development of education in NU, which has long been known for its religious education model, both in the form of pesantren and madrasah. Specifically, this study aims to map the changes that have occurred in PTNU since the reform era in Indonesia. This study is a qualitative research using data collection including documents, interviews, and observations. This research found that there was an attempt to centralize management with the establishment of the Nahdlatul Ulama Higher Education Institution by the Nahdlatul Ulama Executive Board (PBNU), a significant increase in the number of general study programs, and demographic changes on the PTNU campus so that it became more heterogeneous from a religious background. The conclusion of this research is that the reform era became an era of change in PTNU from the management of educational institutions on a local scale to a national scale, changes in the type of religious universities towards general universities, and changes in campus residents who were originally homogeneous to heterogeneous. The development and changing trends in PTNU are evidence of the appropriation process in PTNU which absorbs external values and is modified so that PTNU can grow and develop in line with the times.